Political Efficacy and Political Engagement in College Students - Muhammad Zulfa Alfaruqy (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
College students are agents of change who are expected to participate and contribute to the nation and state. Students with their idealism are required to be actively engaged in influencing the process and making political decisions that have an impact on public policy. This study aims to examine the relationship between political efficacy and political engagement in college students, and to understand the motivation for political engagement. This study uses a mixed method consisting of quantitative comparison and qualitative description. This study involved 345 students from the cluster of Science and Technology at Diponegoro University to fill out the instruments, of which 3 students were assigned in the interview process. The first stage is data collection using the Political Efficacy Scale (α = 0.852, 11 items) and the Political Engagement Scale (α = 0.862, 16 items). Afterward, the second stage is data collection using in-depth interviews. The results of the study show that there is a significant positive relationship between political efficacy and political engagement in students. The correlation coefficient is 0.456 with a significance of 0.000 (p-value <0.05). Political efficacy makes an effective contribution of 20.8% to political engagement. The motivation for political engagement is personal awareness, perceived political effects, reinforcement from social environment, and uncertainty avoidance. This research has implications for the urgency of student awareness and the role of the social environment of students in fostering political engagement.Mahasiswa merupakan agen perubahan yang diharapkan turut serta berkontribusi bagi bangsa dan negara. Mahasiswa dengan idealismenya dituntut terlibat aktif dalam mempengaruhi proses dan pengambilan keputusan politik yang berdampak pada kebijakan publik. Penelitian ini bertujuan untuk menguji hubungan antara efikasi politik dengan keterlibatan politik pada mahasiswa, serta memahami motivasi keterlibatan politiknya. Penelitian menggunakan metode campuran (mixed method) yang terdiri dari kuantitatif komparatif dan kualitatif deskriptif. Penelitian melibatkan 345 mahasiswa dari rumpun ilmu sains dan teknologi (saintek) Universitas Diponegoro dalam pengisian skala, di mana 3 mahasiswa di antaranya dilibatkan dalam proses wawancara. Tahap pertama, penggalian data menggunakan Skala Efikasi Politik (α= 0,852, 11 aitem) dan Skala Keterlibatan Politik (α= 0,862, 16 aitem). Tahap kedua, penggalian data menggunakan wawancara mendalam. Hasil penelitian menunjukkan bahwa terdapat hubungan positif signifikan antara efikasi politik dengan keterlibatan politik pada mahasiswa. Koefisien korelasi sebesar 0.456 dengan signifikansi 0.000 (p < 0.05) Efikasi politik memberi sumbangan efektif sebesar 20,8% terhadap keterlibatan politik. Motivasi keterlibatan politik adalah kesadaran personal, efek politik yang dirasakan, penguatan lingkungan sosial, dan pengindaran ketidakpastian. Penelitian ini berimplikasi pada urgensi kesadaran mahasiswa dan peran lingkungan sosial mahasiswa dalam menumbuhkan keterlibatan politik.